Bergaptol Ameliorates Insulin Sensitivity in Gestational Diabetes Mellitus by Inhibiting the Inflammatory Pathway in Streptozotocin-Induced Diabetic Rats - Li, Q; Chen, J; Wang, Z; Zhuang, L; Yu, Z; Yang, D (Physiological research, 2025)
Investigation determines the beneficial effect of bergaptol against gestational diabetes (GD). Gestational diabetes was induced in female rats and treated them with bergaptol 20 and 40 mg/kg for eighteen days. Effect of bergaptol was assessed on blood glucose and insulin level in GD rat. Inflammatory mediators and oxidative stress parameters were also assessed in GD rats. Moreover, mRNA expression of INSR, NF-kappaB, Akt and GSK-3beta were assessed in the GD rats by qRT-PCR method. In silico network pharmacology study was performed, along with gene ontology and egg pathway to assessed the targets of bergaptol, molecular docking study was also performed for the confirmation of possible pathway involved in the management of GD. Blood glucose and insulin level was significantly reduces in the blood bergaptol treated group than GD group of rats. Treatment with bergaptol ameliorates the altered level of mediators of inflammation and oxidative stress parameters in GD rats. There was significant reduction in the mRNA expression of NF-kappaB and GSK-3beta and increase in expression of INSR and Akt in the tissue homogenate of bergaptol treated GD rats. Docking study shows effective binding strength of bergaptol individually with INSR, NF-kappaB, Akt and GSK-3beta-protein targets. In conclusion, data of investigation suggest that bergaptol improves the sensitivity of insulin receptor in GD, as it reduces parameters of oxidative stress and inflammatory mediators by regulating INSR/NF-kappaB/Akt/GSK-3beta pathway. Key words Gestational diabetes, Bergaptol, Insulin resistance, Inflammation, Oxidative stress.
Keywords: oxidační stres; Insulin Resistance; inzulinová rezistence; Rats, Wistar; Inflammation; experimentální diabetes mellitus; streptozocin; mediátory zánětu; Pregnancy; krevní glukóza; těhotenství; signální transdukce; Molecular Docking Simulation; potkani Wistar; Signal Transduction; Streptozocin; zánět; krysa rodu Rattus; simulace molekulového dockingu; Diabetes, Gestational; Animals; gestační diabetes; ženské pohlaví; zvířata; Rats; Diabetes Mellitus, Experimental; Inflammation Mediators; Female; Oxidative Stress; Blood Glucose